POTENSI LIMBAH KULIT UDANG SEBAGAI SUMBER NUTRISI BAGI PERTUMBUHAN Metarhizium anisopliae YANG DIUJIKAN PADA NYAMUK Aedes aegypti - Witiyasti Imaningsih; Muhamat Muhamat; Nova Anisa’a (Universitas Lambung Mangkurat, 2020)
Shrimp shell waste is a waste from the shrimp freezing production process. Shrimp shell waste has the potential to be a source of nutrients for the growth and virulence of Metarhizium anisopliae. This study aims to calculate the amount of conidiospores and find out the virulence levels of M. anisopliae grown in PDA media with the addition of nutrient sources (yeast extract, KNO3, and media without additional nutrients). In this study the test insect used was the Aedes aegypti mosquito, which was observed every 24 hours for 96 hours. The results showed that the highest amount of conidiospores and virulences were produced by PDA media with the addition of a 0.25% source of nutrients derived from shrimp shell waste.